2018
DOI: 10.1002/jsid.735
|View full text |Cite
|
Sign up to set email alerts
|

A study of contact properties between molybdenum and amorphous silicon tin oxide thin film transistors

Abstract: Amorphous silicon tin oxide (a‐STO) semiconductor is of increasing interest for fabricating thin film transistor. The contact properties of Mo source/drain electrode to a‐STO film subjected to different thermal annealing processes was investigated. The formation of molybdenum oxide interlayer between Mo and a‐STO film annealed in air ambient was confirmed by cross‐sectional transmission electron microscopy image, and the interlayer was formed by getting oxygen from a‐STO film in air annealing process. The form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…With the discharge power of AZTO increasing from 100 W to 120 W, the oxygen vacancy decreases from 17.3 ± 0.8% to 19.0 ± 0.1% and with the discharge power of ZrO 2 increasing from 15 W to 45 W, the content of oxygen vacancy decreases from 19.0 ± 0.1% to 14.1 ± 0.1%. Since it is known that the carriers of oxide semiconductors are related to oxygen vacancy, the Sample B has a highest carrier density [19]. Figure 4 shows the transmittance of the Zr-AZTO thin films of different groups measured by UV-2600.…”
Section: Resultsmentioning
confidence: 99%
“…With the discharge power of AZTO increasing from 100 W to 120 W, the oxygen vacancy decreases from 17.3 ± 0.8% to 19.0 ± 0.1% and with the discharge power of ZrO 2 increasing from 15 W to 45 W, the content of oxygen vacancy decreases from 19.0 ± 0.1% to 14.1 ± 0.1%. Since it is known that the carriers of oxide semiconductors are related to oxygen vacancy, the Sample B has a highest carrier density [19]. Figure 4 shows the transmittance of the Zr-AZTO thin films of different groups measured by UV-2600.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the sustainability analysis, Mo and Fe are seen as promising candidate materials for ZnO TFTs, but understanding it's behaviour as ohmic contacts with ZnO is vital. [20] For instance, Ning et al reported the formation of a molybdenum oxide interlayer between the Mo and a-STO that prevent the diffusion of Mo atoms into a-STO film resulting in a better-quality contact interface [18]. In terms of electrical behaviour, for an ideal metal-semiconductor junction, the barrier height for electron injection (ΦB) depends primarily on the metal work function (ΦM) and the electron affinity of the semiconductor (χS), and is given by the Mott-Schottky equation:…”
Section: B Suitability Of Mo Source/drain Electrode For Znomentioning
confidence: 99%